2017
DOI: 10.1002/asia.201700204
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Bridged Metallodiazaporphyrin Dimers: Synergistic Effects of Nitrogen Bridges and meso‐Nitrogen Atoms on Structure and Properties

Abstract: NH-bridged and pyrazine-fused metallodiazaporphyrin dimers have been prepared from nickel(II) and copper(II) complexes of 3-amino-5,15-diazaporphyrin by Pd-catalyzed C-N cross-coupling and oxidative dimerization reactions, respectively. The synergistic effects of the nitrogen bridges and meso-nitrogen atoms play major roles in enhancing the light-harvesting properties and delocalization of an electron spin over the entire π-skeletons of the metallodiazaporphyrin dimers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…For example, electrodonating meso ‐diarylamino porphyrins are effective photosensitizers for dye‐sensitized solar cells . Recently, we reported P1 and P2 as the first examples of 5,15‐diazaporphyrins (DAPs) bearing an amino group at the periphery (Scheme ) . Notably, P1 (M=Ni, Cu) and P2 (M=Ni) have large charge‐transfer (CT) character, reflecting the high‐lying highest occupied molecular orbital (HOMO) of the peripheral amino group and the low‐lying lowest unoccupied molecular orbital (LUMO) of the DAP ring .…”
Section: Methodsmentioning
confidence: 99%
“…For example, electrodonating meso ‐diarylamino porphyrins are effective photosensitizers for dye‐sensitized solar cells . Recently, we reported P1 and P2 as the first examples of 5,15‐diazaporphyrins (DAPs) bearing an amino group at the periphery (Scheme ) . Notably, P1 (M=Ni, Cu) and P2 (M=Ni) have large charge‐transfer (CT) character, reflecting the high‐lying highest occupied molecular orbital (HOMO) of the peripheral amino group and the low‐lying lowest unoccupied molecular orbital (LUMO) of the DAP ring .…”
Section: Methodsmentioning
confidence: 99%
“…These properties are important in materials science,f or example,f or photodynamic therapy and organic solar cells.The introduction of an amino group on aporphyrin ring is areliable strategy for achieving high lightharvesting ability in the long-wavelength region. [3] Notably, P1 (M = Ni, Cu) and P2 (M = Ni)have large charge-transfer (CT) character,reflecting the high-lying highest occupied molecular orbital (HOMO) of the peripheral amino group and the low-lying lowest unoccupied molecular orbital (LUMO) of the DAPr ing. [2] Recently,w er eported P1 and P2 as the first examples of 5,15-diazaporphyrins (DAPs) bearing an amino group at the periphery (Scheme 1).…”
mentioning
confidence: 99%
“…[2] Recently,w er eported P1 and P2 as the first examples of 5,15-diazaporphyrins (DAPs) bearing an amino group at the periphery (Scheme 1). [3] We envisioned that the further amination of DAPw ould afford ap romising scaffold for constructing new NIR-light-responsive photosensitizers. [4] As ar esult, P1 and P2 exhibit considerably red shifted CT absorption bands,a t7 00 and 760 nm, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the pioneering work of Crossley et al, [1] pyrrolemodification has been demonstrated to be effective in diversification of porphyrins by producing various pyrrolemodified porphyrins,t he structural, optical, and electrochemical properties of which depend on introduced acyclicor cyclic units. [1,2] Among pyrrole-modification strategies, as equence of pyrrole-ring-cleavage and non-pyrrolic-ringreconstruction has been often used to explore novel pyrrolemodified porphyrins.I nc ontrast to the rich chemistry of pyrrole-modified porphyrins,s uch strategy has been only scarcely accomplished for other porphyrinoids.A sr are examples, [3][4][5] Barrett and Hoffman et al reported the synthesis of seco-porphyrazine by oxidative cleavage of the diaminopyrrole unit in porphyrazine, [3] and Matano et al reported the synthesis of diazaporpholactone by oxidation of 3-aminodiazaporphyrin with m-chloroperbenzoic acid, [4] which is the same procedure used for the synthesis of porpholactone reported by Crossley et al [1] Boron(III) subporphyrins (hereinafter referred to as subporphyrins), genuine ring-contracted congeners of porphyrins,h ave been extensively explored in the last decade because of the attractive attributes such as 14p aromaticity, bowl-shaped structure,b right fluorescence,a nd large substituent effect. [6] Recently,w er eported the synthesis of subsecochlorin dicarboxylic acid 1 and subchlorophin 2 from subporphyrin 0 through cleavage of one pyrrole ring (Scheme 1).…”
mentioning
confidence: 99%